Creating Eco-Friendly Bags to Reduce Plastic Waste and Increase Sale Value - Siska Wijayanti; Elvia Sulmiarini; Vitria Vitria (Indonesian Journal of Multidisciplinary Science, 2022)
Plastic waste has become a common problem in Indonesia. The Indonesian government has actually issued many policies to overcome the impact of plastic waste, but so far the Indonesian government has not succeeded in dealing with plastic waste. Currently, Indonesia has many young generations. As the younger generation in Indonesia, we propose a solution to deal with plastic waste, namely by using environmentally friendly bags made from spun bonds. We also implement the solutions we offer for the children at Rumah Yatim and Dhuafa Islahul Hayat Foundation, Pondok Petir.